ANÁLISIS HISTOLÓGICO DEL RECUBRIMIENTO PULPAR DIRECTO CON PASTA A BASE DE UNCARIA TOMENTOSA. UÑA DE GATO - Lahoud S., Vìctor (2000)
The scientific studies demonstrate comparatively, the advantagese from aplication of Uncaria Tomentosa. Cat's Claw in the direct pulp capping over using hydroxide of calcium. The treatment with Cat's Claw demonstrate to provoke full cicatrisation o injure pulp with abundant colageno and new formations capilares compared with treatment with Dycal he who to provoke cicatrisation most slowness and moderate with medium quantity of colageno and new formations capilares. To him observe minimun inflammation pulp in alls the cases treatment with Dycal and Cat's Claw.